Perencanaan Sistem Pemanenan Air Hujan Skala Rumah Tangga Di Korea Selatan - Ha, Park Eun; Susilo, Gatot Eko; Wahono, Endro Prasetyo (Universitas Lampung, 2018)
South Korea is classified as a water shortage country. The government has been promoting a